Investing in obesity treatment to deliver significant healthcare savings: Estimating the healthcare costs of obesity and the benefits of treatment - Fredrik Erixon; Lisa Brandt; Michal Krol (European Centre for International Political Economy (ECIPE), 2014)
Obesity rates in Europe have been growing at an accelerated speed in the past two decades. In the European Union, between 36.9% and 56.7% of all women - and between 51% and 69.3% of all men - are overweight or obese, according to data from 2008-09. Estimates on the growth of obesity suggest that by 2030, more than 40% of the population in the United Kingdom will be obese. The equivalent rate for Germany is 28.8%. Obesity is a source of several non-communicable diseases. An obese individual is at serious risk of developing diagnosis like diabetes type 2 - and the risk for cardiovascular and respiratory diseases increases considerably with obesity. According to the World Health Organisation, obesity and overweight are estimated to be the principal causes of 44% of all cases of diabetes around the world, 23% of ischaemic heart diseases and between 7-41% of all cancer cases. Consequently, obesity is a source of healthcare expenditures: expenditures to treat patients that have developed diseases associated with obesity. While manageable today, the total healthcare expenditures associated with obesity are likely to grow faster in the next couple of decades than in the past. Increased obesity rates are one factor behind this trend; another is increased longevity. Another way to look at it is that rising healthcare expenditures means that there are potential savings to be made from future expenditures by preventing a higher share of the population to become obese. If existing methodologies to "treat" obesity, like lifestyle weight management programmes, are employed societies can reduce the number of people that is or at risk of becoming obese. The new ECIPE study estimates potential savings in future healthcare expenditures by employing effective weight management programmes today. It also provide estimations on savings that could have been made in the past, had obesity treatments been used.
Keywords: 330